ANALISIS ABNORMAL RETURN SURAT BERHARGA PADA PENAWARAN PERDANA DI BURSA EFEK JAKARTA (PERBANDINGAN PERIODE SEBELUM DAN SELAMA KRISIS MONETER) - Tri Kartika Pertiwi (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
The research about abnormal return of initial offering has  been  carried out by many other researchers. The results indicated that underpricing which signed by positive abnormal returns occurred in the short time. However, the effects that has caused underpricing was still indicate inconsistency. The objective of this research is to examine the differences of abnormal return between company that carry out  initial public offering in the  period  before and during monetary crisis,with a special reference to Jakarta Stock Exchange. Furthermore, it also aims to find out effects of stock value uncertainty and company value that proxied by standard deviation and age, effect of informed demand proxied by delay time, and effect of underwriter reputation on abnormal return.Results indicated that there was significant abnormal return difference between the periods before and during monetary crisis.  The factor that effected abnormal return in the period before monetary crisis was delay variable and underwriter reputation. The results was contrary with initial assumption. The significant factor that influenced abnormal return in the period during monetary crisis was standard deviation and age